2002
DOI: 10.1177/0145482x0209600902
|View full text |Cite
|
Sign up to set email alerts
|

Employment after Vision Loss: Results of a Collective Case Study

Abstract: A collective case study approach was used to examine factors that influence the job retention of persons with vision loss. It was found that computer technology was a major positive influence and print access and technology were a source of stress for most participants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
1
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 1 publication
3
30
1
2
Order By: Relevance
“…Third, our findings with respect to external, non-work resources and their salience in work settings play a significant role in the strain experience (Hobfoll, 2001), open up a promising avenue, insofar as they show that family support, a known positive source of support for workers with disabilities (Crudden, 2002;Kelley & Lambert, 1992;P erez et al, 2015), can have paradoxical effects. Our results show that in workers with disabilities employed in ordinary jobs family support may be counterproductive when he/she experiences medium to high levels of burnout, because this external support accentuates vulnerability to work strain and perceptions of a lack of work resources (POS) with which to combat the stresses and demands of the job.…”
Section: Implications For Theory and Researchmentioning
confidence: 76%
See 1 more Smart Citation
“…Third, our findings with respect to external, non-work resources and their salience in work settings play a significant role in the strain experience (Hobfoll, 2001), open up a promising avenue, insofar as they show that family support, a known positive source of support for workers with disabilities (Crudden, 2002;Kelley & Lambert, 1992;P erez et al, 2015), can have paradoxical effects. Our results show that in workers with disabilities employed in ordinary jobs family support may be counterproductive when he/she experiences medium to high levels of burnout, because this external support accentuates vulnerability to work strain and perceptions of a lack of work resources (POS) with which to combat the stresses and demands of the job.…”
Section: Implications For Theory and Researchmentioning
confidence: 76%
“…Existing research has found that family support is also important to explaining disabled worker's attitudes (Amstad, Meier, Elfering & Semmer, 2011;Ferguson, Carlson, Zivnuska & Whitten, 2012;P erez, Alcover & Chambel, 2015) and to their adjustment to work, because it boosts motivation and confidence (Crudden, 2002;Kelley & Lambert, 1992). Initially, the measurement of family support depended on the size of the family network, considered as indicator of social support (e.g., Stokes, 1983).…”
Section: Family Support and Workers With Disabilitiesmentioning
confidence: 99%
“…The underlying factors for employment of people with visual impairment identified in prior research are: a higher level of education, an employment quota system, personal traits, and good social support of family and/or social networks (Capella-McDonnall, 2005;Cimarolli & Wang, 2006;Crudden, 2002;Kef & Dekovic, 2004;Kef, Hox, & Habekothe, 2000;Kirchner, Schmeidler & Todorov, 1999;McDonnall, 2010;McDonnall & Crudden, 2009;Roy, Dimigen & Taylor, 1998). In a study conducted by McDonnall and Crudden (2009), academic competence was one of the factors affecting successful employment of youths with visual impairments in the United States.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These challenges include unfair hiring practices (Crudden, McBroom, Skinner, & Moore, 1998;McMahon, Jaet, & Shaw, 1995;Rumrill & Scheff, 1997;Tedder & McBroom, 1989), negative attitudes by employers (Berry & Meyer, 1995;Crudden et al, 1998;Frank, 2003;Kirchner, Johnson, & Harkins, 1997), the lack of availability of transportation to the work site (Crudden et al, 1998;Frank, 2003;Kirchner, Harkins, & Esposito, 1991;, and difficulty locating information about potential jobs (Crudden et al, 1998). They also include the inability to read printed material (Crudden et al, 1998;Frank, 2003), difficulty identifying and obtaining accommodations for acquiring and performing jobs (Crudden et al, 1998;Frank, 2003;McMahon et al, 1995), and alienation and resistance from coworkers (Crudden & Fireson, 1997;Frank, 2003;Lee, 1996).…”
Section: Employment Concerns Of Americans Who Are Visually Impairedmentioning
confidence: 99%